2017
DOI: 10.24831/jai.v44i3.12787
|View full text |Cite
|
Sign up to set email alerts
|

Keragaman Genetik Kacang Bogor (Vigna subterranea L. Verdc.) Berdasarkan Marka SSR (Simple Sequence Repeat)

Abstract: <em></em><em>ABSTRACT<br /><br />Bambara groundnut (Vigna subterranea L. Verdc.) is an important underutilized legume crop in Indonesia. The aim of this research is to study genetic diversity of bambara groundnut from Sukabumi and Sumedang, West Java, Indonesia. This study used 107 bambara groundnut accessions, which consisted of 57 accessions from Sukabumi and 50 accessions from Sumedang. We use five simple sequence repeat (SSR) to analyze the accessions. Totally nine alleles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Berdasarkan penelitian tersebut, kacang bogor memiliki bentuk biji bulat dan oval, sementara warna bijinya ungu tua, coklat muda, merah tua, merah terang, dan coklat tua. Menurut Illahi (2015), keragaman genetik kulit biji a b a b kacang bogor asal Sukabumi lebih rendah dibandingkan kacang bogor asal Sumedang. Kacang bogor asal Sukabumi memiliki warna kulit biji coklat dan hitam, sedangkan kacang bogor asal Sumedang memiliki kulit biji warna krem, coklat, hitam keunguan dan hitam.…”
Section: Karakter Morfologiunclassified
“…Berdasarkan penelitian tersebut, kacang bogor memiliki bentuk biji bulat dan oval, sementara warna bijinya ungu tua, coklat muda, merah tua, merah terang, dan coklat tua. Menurut Illahi (2015), keragaman genetik kulit biji a b a b kacang bogor asal Sukabumi lebih rendah dibandingkan kacang bogor asal Sumedang. Kacang bogor asal Sukabumi memiliki warna kulit biji coklat dan hitam, sedangkan kacang bogor asal Sumedang memiliki kulit biji warna krem, coklat, hitam keunguan dan hitam.…”
Section: Karakter Morfologiunclassified
“…Simple sequence repeat markers are developed by amplifying the targeted SSR sequences using PCR. Copyright © 2019 Universitas Brawijaya Many studies have shown the presence of a high allelic variation among different plant populations (Illahi, Wiendi, & Sudarsono, 2016;Larekeng, Purwito, Mattjik, & Sudarsono, 2018;Oktavia, Kuswanhadi, Dinarty, Widodo, & Sudarsono, 2017;Purwoko, Cartealy, Tajuddin, Dinarti, & Sudarsono, 2019;Sulistiyorini, Rubiyo, & Sudarsono, 2018). The SSR markers are used as powerful tools for supporting plant breeding of many perennial crops, including oil palm (Ajambang, Sudarsono, Asmono, & Toruan, 2012;Budiman, Apriyanto, Pancoro, & Sudarsono, 2019;Larekeng, Maskromo, Purwito, Matjik, & Sudarsono, 2015;Maskromo, Larekeng, Novarianto, & Sudarsono, 2017;Natawijaya et al, 2019;Tinche, Asmono, Dinarti, & Sudarsono, 2014).…”
Section: Introductionmentioning
confidence: 99%